The ABCG2 multidrug transporter is a pump gated by a valve and an extracellular lid - Narakorn Khunweeraphong (Nature Portfolio, 2019)
The human ATP-binding cassette transporter ABCG2 plays critical roles in anticancer resistance but the molecular mechanism of ABCG2-mediated substrate transport remains enigmatic. Here authors use extensive mutagenesis and molecular dynamics simulations to reveal a mechanistic basis for the function of the di-leucine valve and the roof organization in the transport cycle.